NEW DATA ON SR-AND C-ISOTOPIC CHEMOSTRATIGRAPHY OF THE UPPER RIPHEAN TYPE SECTION (SOUTHERN URALS) - Kuznetsov A.B.; Gorokhov I.M.; Semikhatov M.A.; Kislova I.V.; Maslov A.V.; Krupenin M.T.; Prasolov E.M. (My University, 2006)
New data on Sr-and C-isotopic systematics of carbonate rocks from the Upper Riphean stratotype (Karatau Group of the southern Urals) are obtained for several southwestern sections of the Bashkirian meganticlinorium, which have not been studied before. The results obtained supplement the Sr-and C-isotopic information for the group upper horizons thus detailing chemostratigraphic characterization of the entire succession. Limestone and dolostone samples used to analyze the Sr isotope composition satisfy strict geochemical criteria of the isotopic system retentivity and have been subjected to preliminary treatment in ammonium acetate to remove secondary carbonate phases. Data on 255 samples of carbonate rocks (171 studied for the first time) show that δ13C value varies in the Karatau Group succession from -2.8 to +5.9 V-PDB with several in-phase excursions from the general trend in all the sections studied in the area 90 × 130 km. The δ13C variation trend demarcates several levels in the carbonate succession of the Karatau Group suitable for objectives of regional stratigraphy and for C-isotope chemostratigraphic subdivision of the Upper Riphean. The results of Sr isotopic analysis of 121 samples (51 unstudied before) from the Karatau Group imply that rocks in its lower part (the Katav Formation and basal horizon of the Inzer Formation) experienced considerable secondary alterations, while limestones and dolostones of the overlying interval of the group are frequently unaltered. In the "best" samples satisfying geochemical criteria of the isotopic system retentivity, the 87Sr/86Sr initial ratio increases from 0.70521-0.70532 in the lower Inzer deposits to 0.70611 in the upper Min'yar carbonates, decreasing to <0.70600 near the top of the latter. Above the regional hiatus separating the Min'yar and Uk formation, this ratio grows from 0.70533 to 0.70605-0.70609 in the limestone succession of the last formation. © MAIK "Nauka/Interperiodica" 2006.
Keywords: δ13C VARIATIONS; 87SR/86SR RATIO; KARATAU GROUP; SOUTHERN URALS; SR-AND C-ISOTOPIC CHEMOSTRATIGRAPHY; UPPER RIPHEAN; Докембрий::Протерозой::Рифей; Precambrian::Proterozoic::Riphean